The blind side [videorecording (DVD)] - Hancock, John Lee; Bullock, Sandra; McGraw, Tim; Aaron, Quinton, 1984-; Head, Jae; Collins, Lily, 1989-; Bates, Kathy, 1948-; Burwell, Carter; Lewis, Michael (Michael M.) (Distributed by Warner Home Video, 2010)
Michael Oher is a homeless African-American teenager who is from a broken home. Mike is taken in by the Touhys, a well-to-do white family who help him fulfill his potential. At the same time, Oher's presence in the Touhys' lives leads them to some insightful self-discoveries of their own. Living in his new environment, Mike faces a completely different set of challenges to overcome - as both a football player and student. Mike works hard and, with the help of his coaches and adopted family, becomes an All-American offensive left tackle.